2014
DOI: 10.1098/rsta.2013.0380
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional multi-scale model of deformable platelets adhesion to vessel wall in blood flow

Abstract: When a blood vessel ruptures or gets inflamed, the human body responds by rapidly forming a clot to restrict the loss of blood. Platelets aggregation at the injury site of the blood vessel occurring via platelet–platelet adhesion, tethering and rolling on the injured endothelium is a critical initial step in blood clot formation. A novel three-dimensional multi-scale model is introduced and used in this paper to simulate receptor-mediated adhesion of deformable platelets at the site of vascular injury under di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 53 publications
(162 reference statements)
0
52
0
Order By: Relevance
“…The solid phase includes erythrocytes, plasma and leukocytes; therefore it complicates the calculations and is not necessary in our model [38,39,40,41]. Moreover, we observed that prediction of stroke formation is directly associated with blood pressure distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The solid phase includes erythrocytes, plasma and leukocytes; therefore it complicates the calculations and is not necessary in our model [38,39,40,41]. Moreover, we observed that prediction of stroke formation is directly associated with blood pressure distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The SCE method has been introduced to study multi-cellular systems [41], and used for modeling epithelial cell growth [42], platelets in blood flow [43, 44], and gliding bacteria [40]. In this approach, cells are represented as a collection of interconnected subcellular elements.…”
Section: Biologically Calibrated Computational Modelmentioning
confidence: 99%
“…Wu et al [86] presented a three-dimensional multi-scale platelet–blood flow–vessel wall interaction model, which combined three biological scales crucial for the early platelet aggregation. The model included hybrid cell membrane submodel of platelet elasticity, stochastic receptor–ligand binding submodel of cell adhesion kinetics and Lattice Boltzmann submodel of blood flow.…”
Section: Integrative Multi-scale Modeling Approachesmentioning
confidence: 99%
“…c The effect of platelet membrane stiffness on the platelet pause time. (Originally published in Ref [86] Open Access: http://rsta.royalsocietypublishing.org/content/372/2021/20130380.long)…”
Section: Fig 51mentioning
confidence: 99%